2023
DOI: 10.1186/s12889-023-16367-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary carotenoids intake and chronic constipation in American men and women adults: a cross-sectional study

Jiangnan Wang,
Wanru Kong,
Min Liu
et al.

Abstract: Background Dietary carotenoids have been proven to improve intestinal disorders like inflammatory bowel disease and colon cancer, yet little is known about the link between dietary carotenoids and constipation. This study aims to examine the relationship between dietary carotenoids intake and constipation, using data from the National Health and Nutrition Examination Survey (NHANES) 2005–2010. Methods A total of 11,722 participants were enrolled. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Despite the mounting evidence implicating antioxidants in constipation, the influence of gender on the outcomes remains uncertain. A recent study has shown that increasing intake of lycopene can improve intestinal function in men ( 37 ), providing further support for the existence of gender differences, as demonstrated by our research. Elevating CDAI levels is inclined to afford protection against constipation symptoms in males but not in females, mirroring the higher prevalence of constipation among females.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the mounting evidence implicating antioxidants in constipation, the influence of gender on the outcomes remains uncertain. A recent study has shown that increasing intake of lycopene can improve intestinal function in men ( 37 ), providing further support for the existence of gender differences, as demonstrated by our research. Elevating CDAI levels is inclined to afford protection against constipation symptoms in males but not in females, mirroring the higher prevalence of constipation among females.…”
Section: Discussionsupporting
confidence: 89%